Fullerene Reinforced Polymeric Nanocomposites for Energy Storage—Status and Prognoses - Kausar, Ayesha (Frontiers in Materials, 2022)
This review deals with the progress in the field of polymer/fullerene nanocomposites particularly for the energy storage applications. Fullerene is a unique zero dimensional nanocarbon nanomaterial. Fullerene proposes several unique structural, optical, electrical, thermal, mechanical and other superior physical features to the polymeric nanocomposites. Consequently, the high performance polymer/fullerene nanocomposites result from the amalgamation of the unique characteristics of fullerene with the functional polymers. Here, the advancements in the polymer/fullerene nanocomposites regarding their processing and properties, especially the electrical conductivity, charge storage capacities, charge density, power density, charge-discharge, and cyclic performance have been discussed. Moreover, the future and challenging prospects have been summarized anticipating the progress in the field of polymer/fullerene-based energy storage technology.